An Exploration into Akan Traditional Patterns of Learning and its Significance for Contemporary Akan Christian Formation - Kwabena Opuni-Frimpong (Noyam Journals, 2023)
The study is an exploration into the Akan traditional patterns of learning and how it provides educational resources to contemporary Akan Christian formation. It engages some renowned Akan Christian scholars in reflections on the pre-missionary Akan traditional learning patterns before their encounter with the Western missionaries in observation and interviews. The indigenous knowledge systems like the rites of passage remain available educational resources that must attract the intellectual considerations of Akan Christian educators. As qualitative in its methodology, the study examined available materials on the subject and conducted interviews with some individuals who were considered to have significant insights on the subject. The study has noted that Akan traditional patterns of learning possess relevant information that must be considered by the church in its quest for relevant contemporary patterns of Christian formation in African Christianity. Traditional Patterns of Learning, it is recommended, must attract academic examination and research to unearth the deep-seated worth of intellectual weight that has not attracted thorough Christian consideration due to the European-value setting for Western missionary established churches among the Akan people of Ghana.